2019
DOI: 10.14573/altex.1811011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in chemico skin sensitization methods and development of an in chemico skin photosensitization assay

Abstract: US), recommend multiple integrated testing strategies (ITS) using non-animal test batteries that combine in silico, in chemico, and in vitro methods to identify skin allergens (EURL ECVAM,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These studies can be useful for understanding certain aspects of photobinding steps that will help researchers to design future potential in silico models, but do not provide real progress in the field of photosafety assessment. The other four adapt ADRA [44,45] or DPRA [42,44,46] assays to identify contact sensitizers by coupling UVA lamps. The assays proved to be transferable among laboratories experienced in conducting high-performance liquid chromatography analysis [61].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies can be useful for understanding certain aspects of photobinding steps that will help researchers to design future potential in silico models, but do not provide real progress in the field of photosafety assessment. The other four adapt ADRA [44,45] or DPRA [42,44,46] assays to identify contact sensitizers by coupling UVA lamps. The assays proved to be transferable among laboratories experienced in conducting high-performance liquid chromatography analysis [61].…”
Section: Discussionmentioning
confidence: 99%
“…The assays proved to be transferable among laboratories experienced in conducting high-performance liquid chromatography analysis [61]. Taking into consideration that among the four studies, almost 70 different chemicals besides allergen mixtures and herbicide formulations had been assessed, it has been proven that the volume of reaction [42], irradiation and time of incubation [44] can be lowered, and therefore these photoassays are promising tools for photosafety assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as the ADRA is superior to DPRA in many aspects as described above, establishing a test based on ADRA is expected to enable the efficient evaluation of the photoallergy potential of compounds with various properties. Patel et al () have suggested the usefulness of photo‐DPRA and photo‐ADRA by applying DPRA and ADRA. However, because the photo‐ADRA reported by them requires the test chemical solution to be prepared at 100 mM, similar to DPRA, the advantages, such as solubility and precipitation of test chemical in reaction buffer, of preparing the test chemical solution at 1 mM in photo‐ADRA, as proposed by us, may be lost.…”
Section: Introductionmentioning
confidence: 99%